(3QSGdI aj GdJhMjOs - (3eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj GdCUagGfj, J (B1111 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Sgd dfG Sdhc TQGFY GdOjf CeG HYO ajbhd eMeO Jbi eMeO HGbQ bO SCdfi HYV ai GdPi ETJHg Ydi GdfGS s
(3BNQgG (B:s
(3cGf jcage ai YbGFOge GdHGWdI hdjcf gPg BNQ eG CQOfG EjQGOg ai gPI GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B91s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs